Observations of Terra Nova Bay polynya by RadarSAT-2: Dual-and single-polarization methods - Nunziata, F.; Buono, A.; Moctezuma-Flores, M.; Parmiggiani, F.; Migliaccio, M. (2017 IEEE 3rd International Forum on Research and Technologies for Society and Industry (RTSI), 2017)
In this study, dual-polarimetric (DP) Synthetic Aperture Radar (SAR) data collected by the RadarSAT-2 SAR mission in Antarctica are exploited to observe Terra Nova Bay (TNB) polynya, Ross Sea, Antarctica. Single-polarization segmentation and a dual-polarimetric classification scheme are adopted to analyze the polynya. Experimental results show that single-polarization segmentation allows correctly extracting polynya; while dual-polarimetric information provides additional information that allows a rough classification according to the dominant scattering mechanism that characterizes the observed scene.